ANALISIS PERSEPSI DAN SIKAP KONSUMEN DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KARTU PERDANA XL DI SUMBAWA BESAR - Damayarsi, Desta; Sutanty, Marisa (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to know the effect of perceptions and attitudes of consumers on purchasing decisions of XL prime card in communities of Sumbawa Besar City. The type of this study was associative. The type of data used is quantitative data in the form of respondents' responses in answering the questions given. This quantitative data was obtained directly from primary sources, namely the users of XL prime card in Sumbawa Besar City. The population of XL prime card users in the city of Sumbawa Besar is 156.752 people, while the sample selected as respondents is 100 people who are determined using the Slovin formula. The data used in this research was collected using a questionnaire. The data that has been collected is processed using the SPSS application and then analyzed using multiple linear regression analysis techniques, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that the perceptions and attitudes of consumers had a positive and significant effect on purchasing decisions of XL prime card in communities of Sumbawa Besar City, both partially and simultaneously. Consumer perceptions and attitudes have quite a large ability to influence changes in purchasing decisions of XL prime card in communities of Sumbawa Besar City was 60.1%, while the remaining 38.9% was affected by other variables outside this research model.